2016
DOI: 10.1002/ldr.2602
|View full text |Cite
|
Sign up to set email alerts
|

Management of Grazing Intensity in the Semi‐Arid Rangelands of Southern Australia: Effects on Soil and Biodiversity

Abstract: Overgrazing contributes to rangeland degradation altering plant community composition, erosion and biodiversity. Little unanimity in the literature exists on the effects of livestock grazing on soil carbon and biodiversity, in part, due to uncontrolled grazing pressure from native and feral animals. Paired paddock contrasts at three, long‐term (>8 years) study locations in the southern Australian rangelands were used to examine the effects of managing grazing intensity through the use of exclusion fencing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…The damage of the soil structure and the expansion of open surfaces may cause an increased rate of erosion and deflation (Lu et al, 2017). Grazing can also influence the organic matter content of the soil affecting decisive processes of mineralization and decomposition (Peco, Navarro, Carmona, Medina, & Marques, 2017;Waters, Orgill, Melville, Toole, & Smith, 2017;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The damage of the soil structure and the expansion of open surfaces may cause an increased rate of erosion and deflation (Lu et al, 2017). Grazing can also influence the organic matter content of the soil affecting decisive processes of mineralization and decomposition (Peco, Navarro, Carmona, Medina, & Marques, 2017;Waters, Orgill, Melville, Toole, & Smith, 2017;Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Participants in this case study did not consider it appropriate to this context, despite the fact that it is commonly recommended for rangelands overseas (Liniger et al 2011, Nkonya et al 2011 and Australian results have indicated potential benefits for groundcover and plant diversity on certain rangeland soil types (Waters et al 2017).…”
Section: Discussionmentioning
confidence: 95%
“…If optimisation increases system complexity (e.g. rotational or mob grazing), time costs may be incurred (Waters, Orgill, Melville, Toole, & Smith, 2017).…”
Section: Private Financial Barriers and Incentives (Yield Maintenancmentioning
confidence: 99%